Color‐Selective Printed Organic Photodiodes for Filterless Multichannel Visible Light Communication. Issue 12 (18th February 2020) - Strobel, Noah; Droseros, Nikolaos; Köntges, Wolfgang; Seiberlich, Mervin; Pietsch, Manuel; Schlisske, Stefan; Lindheimer, Felix; Schröder, Rasmus R.; Lemmer, Uli; Pfannmöller, Martin; Banerji, Natalie; Hernandez‐Sosa, Gerardo
Abstract: Future lightweight, flexible, and wearable electronics will employ visible‐light‐communication schemes to interact within indoor environments. Organic photodiodes are particularly well suited for such technologies as they enable chemically tailored optoelectronic performance and fabrication by printing techniques on thin and flexible substrates. However, previous methods have failed to address versatile functionality regarding wavelength selectivity without increasing fabrication complexity. This work introduces a general solution for printing wavelength‐selective bulk‐heterojunction photodetectors through engineering of the ink formulation. Nonfullerene acceptors are incorporated in a transparent polymer donor matrix to narrow and tune the response in the visible range without optical filters or light‐management techniques. This approach effectively decouples the optical response from the viscoelastic ink properties, simplifying process development. A thorough morphological and spectroscopic investigation finds excellent charge‐carrier dynamics enabling state‐of‐the‐art responsivities >10 2 mA W −1 and cutoff frequencies >1.5 MHz. Finally, the color selectivity and high performance are demonstrated in a filterless visible‐light‐communication system capable of demultiplexing intermixed optical signals. Abstract : Color‐selective organic photodiodes are inkjet printed using a novel photoactive material system based on nonfullerene acceptors. This material system simplifies process development and at the same time enables a high degree of color tunability. Energetic and morphological properties are investigated and the color‐selective devices are employed in a multichannel visible‐light‐communication system.